Hazardous wastes and waste generation factors for plastic products manufacturing industries in Turkey - Oncel, Mehmet Salim; Bektas, Nihal; Bayar, Senem; Engin, Guleda; Caliskan, Yasemin; Salar, Lalehan; Yetis, Ulku (ELSEVIER SCIENCE BV, 2017)
A project titled Hazardous Waste Management in Compliance with European Union Environmental Regulations in Turkey was carried out with the support of The Scientific and Technological Research Council of Turkey on behalf of the Ministry of Environment and Urban Planning in Turkey. In this project, several industries were examined for improving an internet based system called Hazardous Waste Declaration System (HWDS) and meeting the requirements of Turkey. Hazardous waste lists and hazardous waste generation quantities per unit manufacturing (hazardous waste generation factors, HWGFs) for the plastic product manufacturing industry were determined based on the data obtained from these studies. At the same time, declarations of hazardous waste generation quantity made by the organizations in this industry in 2009 and 2010 to HWDS and the literature data were evaluated and the range of HWGFs was created by assessing possible minimum and maximum quantities for each waste. This paper presents the results of the studies conducted in plastic product manufacturing industry in Turkey. The waste lists determined along with the HWGF ranges are presented. HWGFs for manufacturing processes in the plastic industries were calculated in the range of 11.5-100 kg t(-1) in this study and can be used to calculate the amount of hazardous waste for other similar process in the plastic industries. Therefore, it is believed that the results of the study will be useful for determining the types and quantities and the management of hazardous wastes generated by similar plastic product manufacturing industries in the developing world. (C) 2017 Chinese Institute of Environmental Engineering, Taiwan. Production and hosting by Elsevier B.V.
Keywords: Hazardous waste; Hazardous wastes generation factor; Plastic sector; Hazardous waste management; MANAGEMENT; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology